The Effect Of Service Quality, Place And Promotion On Purchasing Decisions For Yamaha N-Max Motorbikes At Ksm Nanga Pinoh Melawi Regency - Heru Prawira; Helman Fachri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of service quality, location, and promotion on purchasing decisions. Data collection was conducted through questionnaires, and to ensure the accuracy and reliability of the questionnaires, two test tools were used, namely validity test and reliability test. In the analysis, multiple linear regression was used to evaluate the relationship between the dependent variable (purchase decision) and independent factors (service quality, location, and promotion). The results showed that location, advertising, and service quality all had a significant impact on consumers purchasing decisions. With a significance level of 0.000 and a calculated F-value of 504.080, the F-test shows that together these independent factors have a major influence on purchasing decisions. The value of the coefficient of determination (R2) indicates that the three independent variables can explain 94.0% of the variance of the purchase decision. The study emphasizes the importance of service quality, location, and promotion in shaping customer behavior, as well as providing valuable insights for companies looking to improve their marketing strategies.